Knowledge: Fast Shower or Slow Vessel Bath? (2010)
The article presents the relationship between childhood, youth and knowledge that EAFIT Children's University intends to promote through a metaphor: children and young people should not receive knowledge as receiving water coming from a shower; instead, they should construct it actively, as in a Colombian traditional bath with a vegetable vessel (totumo) that demands active engagement